MO049: Correlation of Findings in Urinary Sediment Microscopy and Histological Lesions in Kidney Biopsy: Red Flags Not to be Missed. (3rd May 2022) - Barata, Rui; Navarro, David; Moreira Fonseca, Nuno; Carina Ferreira, Ana; Góis, Mário; Viana, Helena; Nolasco, Fernando
Abstract: BACKGROUND AND AIMS: Urinary sediment (U-Sed) is a noninvasive laboratory test that can be performed by an automated analyzer or manually by trained personnel. Manual U-Sed remains the diagnostic standard because it excels at distinguishing isomorphic from dysmorphic red blood cells, identifying renal tubular epithelial cells, lipids, crystals and the composition of casts. Findings in U-Sed reflect damage that is occurring within the kidney, which can be documented by kidney biopsy. This study aimed to investigate the prevalence of a complete profile of U-Sed particles and its associations with histological lesions on kidney biopsy, regardless of renal diagnosis. METHOD: This retrospective study included 131 patients who had contemporary manual U-Sed evaluation and kidney biopsy at our institution, from 2018 to 2021. Renal transplant patients were excluded. A comprehensive set of urinary particles and histological lesions were quantified, and we analyzed their associations. Urinary particles evaluated included casts, erythrocytes, leukocytes, renal tubular epithelial cells, urothelial transitional cells (superficial and deep), lipids, crystals, squamous cells and bacteria. They were semi-quantified from 0 (absent) to 3 + . Renal biopsies samples were reviewed, and a systematic evaluation of 32 histological lesions was performed. When present, lesions were semi-quantified from 0 (absent) to 3 + . Appropriate tests were performed STATA v.16.1. RESULTS: We found an elevated frequency of findings suggestive of proliferative renal disease, such as dysmorphic hematuria ( n = 71, 54.2%), leukocyturia ( n = 62, 47.3%), renal tubular epithelial cells ( n = 53, 40.5%) and lipiduria ( n = 45, 34.4%), and a low frequency of particles evoking urological damage, such as isomorphic hematuria ( n = 29, 22.1%), crystals ( n = 12, 9.2%) and urothelial transitional cells ( n = 26, 9.9%). The association of histological lesions and urinary particles was explored with a multivariate model that identified U-Sed characteristics, which favored the presence of acute tubular necrosis, endocapillary hypercellularity, neutrophils and/or karyorrhexis, wire loops and/or hyaline deposits, fibrinoid necrosis and cellular/fibrocellular crescents (summarized in Table 1 ). CONCLUSION: In a population of patients submitted to kidney biopsy, we found that the presence of some urinary particles (renal tubular epithelial cells, lipids and dysmorphic erythrocytes), which are seldom reported by automated analyzers, conferred an increased likelihood of active proliferative histological lesions. It is important not to misidentify them, as their presence are red flags for relevant proliferative histological lesions. Moreover, given the flare/remission characteristics of proliferative glomerular disease, U-Sed could play a major role in measuring the degree of activity without requiring repeat kidney biopsies.